Frontispiece: Alkynyl Coinage Metal Clusters and Complexes–Syntheses, Structures, and Strategies. Issue 30 (28th May 2018) - Gupta, Arvind Kumar; Orthaber, Andreas
Abstract : Alkynyl ligands exhibit both η 1 (end‐on) and η 2 (side on) modes, including non‐bridged systems, as well as bridging of up to four (or six) metal centres. Herein design principles towards multinuclear homo and hetero‐bi‐metallic coinage metal clusters of alkynyl ligands are summarized and highlighted onpage 7536 ff.